Pentingnya Pemahaman Kode Etik Akuntan dalam Membangun Karakter Akuntan - Evita Fardi Kusuma Dewi; Galih Mulya Subastyan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to investigate the role of the Indonesian Accountant Code of Ethics in guiding the behavior and decisions of accountants, with a focus on the values of integrity, objectivity, competence, and professional behavior. Through a literature review approach, this research method details various relevant data, such as theories, books, articles, and documents related to the ethics of the accounting profession. The results of qualitative analysis indicate that the Indonesian Accountant Code of Ethics, issued by the Indonesian Institute of Accountants (IAI), serves not only as a set of regulations but also as a commitment to building a strong and trustworthy accountant character. Furthermore, the research illustrates the positive impact of ethics and religiosity in shaping the accountant's character, where a deep understanding of moral and ethical values forms a solid foundation for facing ethical dilemmas. Students are identified as key change agents in shaping the future of the accounting profession by understanding the norms and code of ethics of Indonesian accountants. The research's conclusion highlights the need for integrating ethical values, religiosity, and cultural understanding into accounting education to shape students who are not only technically competent but also have high character and integrity. Thus, this research contributes to understanding ethical factors in the accounting profession and emphasizes the importance of holistic education in shaping a more ethical and reliable future accounting profession.